OPTIMALISASI GERAK ANIMASI MODERN DANCE PADA TEKNOLOGI MOTION CAPTURE DENGAN TEKNIK MOTION LAYER MENGGUNAKAN ICLONE 6 PRO - Yosua Jonathan Taringan; Ina Agustina; Fauziah (Jurnal Ilmiah Informatika, 2018)
Motion Capture is an attractive technology for making a movement in the making of movies and games. This technique relies on the recording and motion sampling of an object as data to be transform into 3D form.The purpose of this paper will explain how to optimize movement animation modern dance by using Motion Layer method, presents optimized movement differences that have not been optimized, providing solutions to the creation of animated movements that are still rough. So that can be a reference in the making of movies, 3D animations, or games by combining Motion Capture techniques and Motion Layer method so that every movement produced and shown to be more perfect.